Partial Carpal Arthrodesis in a Warthog (Phacochoerus aethiopicus) - Roe, S. C.; Spelman, Lucy; Spodnick, G.; Loomis, M. (Veterinary and Comparative Orthopaedics and Traumatology, 1994)
A two-year-old male African wart-hog (Phacochoerus aethiopicus) sustained a fracture of the left fourth carpal bone. Initial management consisted of seven weeks of stall rest but moderate lameness continued and fragment displacement was evident on radio-graphs. A partial carpal arthrodesis, involving the intercarpal and carpometacarpal joints, was performed to alleviate discomfort from degenerative joint disease. The joints were stabilized with two bone plates and a cancellous bone graft used to promote arthrodesis. After six weeks of cast support, joint fusion had progressed well. By 24 weeks after surgery, radiographic union was present and the warthog had only mild lameness. Carpal flexion was reduced by approximately 15°. This reduction did not compromise function.A two-year-old African warthog fractured the left fourth carpal bone in a pen injury. Conservative management was unsuccessful. Partial carpal arthrodesis of the intercarpal and carpometacarpal joints was performed using cartilage debridement, cancellous bone grafting, a T-plate and a dynamic compression plate for stabilization. Forelimb function was maintained in an animal that eats and forages while kneeling on its flexed carpus.
Keywords: Partial arthrodesis; carpus; warthog